(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Single-case experimental designs (SCED) are a fundamental tool for scientific research in several areas, especially in Psychology. This article introduces a brief presentation on how to properly construct and analyze data collected with SCED. We highlight data analysis as a process that should lead the researcher to correct decisions and solid conclusions. To this end, it emphasizes aspects related to graphical representation of data, such as visual inspection criteria, and the evaluation of steady states in change phase decision-making. Finally, future perspectives for SCED data analysis are discussed, such as the development of specific research reporting protocols and the use of statistical analyses.